Covalently assembled monolayers of homo- and heteroleptic feII-terpyridyl complexes on SiOx and ITO-coated glass substrates: an experimental and theoretical study - Mondal, Prakash Chandra; Zharnikov, Michael (ChemPhysChem, 2017)
Well-defined FeII-terpyridyl monolayers were fabricated on SiOx and conductive ITO-coated glass substrates through covalent-bond formation between the metallo-organic complexes and a preassembled coupling layer. Three different homo- and heteroleptic complexes with terminal pyridyl, amine, and phenyl groups were tested. All the films were found to be densely packed and homogeneous, and consist of molecules standing upright. They exhibited high thermal (up to ≈220 °C) and temporal (up to 5 h at 100 °C) stability. The UV/Vis spectra of the monolayers showed pronounced metal-to-ligand charge-transfer bands with a significant redshift compared with the solution spectra of the metallo-ligands with a pendant pyridyl group quaternized with the coupling layer, whereas the shift was significantly smaller when the coupling layer was bonded to the primary amine (−NH2) group of the complex. Cyclic voltammograms of the monolayers showed reversible, one-electron redox behavior and suggested strong electronic coupling between the confined molecules and the underlying substrate. Analysis of the electrochemistry data allowed us to estimate the charge-transfer rate constant between the metal center and the substrate. Additionally, detailed quantum-chemical calculations were performed to support and rationalize the experimentally observed photophysical properties of the FeII-terpyridyl complexes both in the solution state and when bound to a SiOx-based substrate.
Gesehen am 26.04.2018
In Titel ist die Zahl II hochgestellt und das Zeichen x tiefgestellt